Distribution and Encounter Rates of Large Herbivores in Chang Chenmo and Daulat Beg Oldi, Ladakh, Jammu and Kashmir, India - Shawl, T.; Takpa, J.; luddin, Hila; Namgail, T. (Our Nature, 2012)
The Ladakh region of the Indian Trans-Himalaya supports twelve large herbivores, including eight mountain ungulates. Many of the species like the Tibetan antelope are highly endangered with rapidly declining populations. Yet there is little information on their status and distributions, especially in remote, inaccessible areas. We report on the status and distribution of five large herbivores in the Chang Chenmo and the Daulat Beg Oldi (DBO) areas of Ladakh, which remain the least known areas in Ladakh in terms of wildlife populations because they are very remote and politically highly sensitive. During the surveys, we observed 246 Tibetan antelopes and 40 blue sheep in DBO. In Chang Chenmo we observed 40 Tibetan antelopes, 2 wild yaks, 42 Tibetan argalis, 67 Tibetan wild asses and 30 blue sheep. In DBO, the encounter rate was higher for the Tibetan antelope (mean = 2.54, SE = 0.63) than the blue sheep (mean = 0.29, SE = 0.19). In Chang Chenmo the highest encounter rate was for the Tibetan wild ass (mean = 0.48, SE = 0.26), whereas the wild yak had the lowest (mean = 0.02, SE = 0.01). Since Chang Cehnmo and DBO are important areas for rare species in India, and are located right at the border with China, there is an urgent need for international collaboration to protect these threatened animals. DOI: http://dx.doi.org/10.3126/on.v9i1.5734